Lithium titanium iron borate positive electrode material as well as preparation method and application thereof

By doping titanium elements into lithium iron borate material, the serious capacity attenuation problem at high magnification is solved, the conductive performance and battery performance are improved, and the use requirements of lithium-ion batteries are met.

CN119503825APending Publication Date: 2025-02-25XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411623089.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The lithium iron borate material has severe capacity decay during charging and discharging test at high magnification, and it is difficult to synthesis of pure phase samples and has low conductivity, which limits its application in lithium-ion batteries.

Method used

By doping titanium elements into lithium iron borate, its ionic conductivity and electron conductivity are improved, the crystal structure is stabilized, grain growth is inhibited, and the deintercalation path of lithium ions is optimized.

Benefits of technology

It improves the conductive performance of lithium iron borate material, enhances the safety, circulation performance and rate performance of ternary batteries, and meets the use requirements of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503825A_ABST
    Figure CN119503825A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a lithium iron titanium borate positive electrode material and a preparation method and application thereof. The preparation method of the lithium iron titanium borate positive electrode material provided by the invention comprises the following steps: carrying out ball-milling mixing on a lithium source, a boron source, a titanium source and an iron source, and then carrying out calcining treatment and crushing treatment to obtain the lithium iron titanium borate positive electrode material. The titanium element is doped with the lithium iron borate, so that the electronic conductivity and the ionic conductivity of the lithium iron borate material can be improved, and the safety, the cycle performance and the rate capability of the ternary battery can be improved after the lithium iron borate material is applied to the ternary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium titanium iron borate positive electrode material and a preparation method and application thereof. Background Art

[0002] In order to solve the energy shortage and air pollution problems that restrict the current economic development, lithium-ion batteries have achieved rapid development in technology research and development, production, and the market in recent years due to their advantages such as high operating voltage, high energy density, long cycle life, no memory effect, small size, light weight, and no environmental pollution, and have formed a large-scale new industry. In the new energy passenger car market, high mileage can not only solve the user's mileage anxiety, but also can obtain high subsidies. Driven by such an environment, ternary lithium batteries have attracted people's attention due to their high specific energy, but the safety performance and cycle performance of nickel cobalt manganese oxide lithium batteries are poor, which limits their wide application in power vehicles.

[0003] Lithium iron phosphate batteries have good room temperature cycle performance, high temperature cycle performance, safety performance, low cost, and environmental friendliness. They have become the most promising lithium-ion batteries for lithium-ion power batteries. However, their theoretical specific capacity is low, about 170mAh / g. Lithium iron borate (LiFeBO3), as a positive electrode active material with a higher specific capacity, has a theoretical specific capacity of up to 220mAh / g, which is greater than the 170mAh / g of lithium iron phosphate. At the same time, it has better conductivity than lithium iron phosphate. These characteristics determine that lithium iron borate has better rate performance and cycle stability. However, lithium iron borate itself also has some disadvantages, such as the difficulty in synthesizing pure phase samples, low intrinsic ionic conductivity and electronic conductivity, especially for unmodified lithium iron borate materials, the capacity decay is extremely serious when charging and discharging at high rates.

[0004] Therefore, how to optimize and improve lithium iron borate materials so that they can meet the requirements of lithium-ion batteries has received more and more attention. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, an embodiment of the present invention provides a lithium titanium iron borate positive electrode material, which is doped with lithium iron borate with titanium to improve the ionic conductivity and electronic conductivity of the lithium iron borate.

[0006] The method for preparing the lithium titanium iron borate positive electrode material of the embodiment of the present invention comprises: mixing a lithium source, a boron source, a titanium source and an iron source by ball milling, and then calcining and crushing to obtain the lithium titanium iron borate positive electrode material.

[0007] The preparation method of the lithium titanium iron borate positive electrode material of the embodiment of the present invention, 1. The preparation method of the embodiment of the present invention adopts titanium element to dope lithium iron borate. Titanium element doping can stabilize the crystal structure, inhibit the secondary growth of grains, accelerate the lithium ion extraction / embedding path, improve the migration efficiency, and can improve the electronic conductivity and ionic conductivity of the lithium iron borate material. After using it in a ternary battery, it can improve the safety, cycle performance and rate performance of the ternary battery; 2. The preparation method of the embodiment of the present invention is simple and easy to operate, has high production efficiency, and is easy to promote and apply in industrial production.

[0008] In some embodiments, the molar ratio of lithium, iron, boron and titanium in the lithium source, iron source, boron source and titanium source is 1:0.5 to 1:0.5 to 1:0.2 to 0.4.

[0009] In some embodiments, the lithium source includes at least one of lithium hydroxide and lithium carbonate;

[0010] And / or, the iron source includes at least one of ferroferric oxide, ferrous oxide, and ferrous oxalate;

[0011] And / or, the boron source includes at least one of boric acid and boron trioxide;

[0012] And / or, the titanium source includes at least one of titanium tetrachloride and titanium dioxide.

[0013] In some embodiments, the ball milling mixing time is 3 to 12 hours;

[0014] And / or, the high temperature calcination temperature is 500-1000° C., and the calcination time is 6-24 hours.

[0015] In some embodiments, the particle size D50 of the lithium titanium iron borate positive electrode material is 0.5-10 μm.

[0016] The embodiment of the present invention also provides a lithium titanium iron borate positive electrode material, which is prepared by the above method.

[0017] The embodiment of the present invention further provides a positive electrode plate, comprising the lithium titanium iron borate positive electrode material prepared by the above method or the above lithium titanium iron borate positive electrode material.

[0018] In some embodiments, the positive electrode plate also includes lithium nickel cobalt manganese oxide.

[0019] In some embodiments, the mass proportion of lithium titanium iron borate positive electrode material in the positive electrode plate is 9.5-28.5%, and the mass proportion of lithium nickel cobalt manganese oxide is 66.5-85.5%.

[0020] An embodiment of the present invention further provides a ternary battery, comprising the above-mentioned positive electrode plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a normal temperature 1C / 1C cycle performance curve of the batteries prepared in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0022] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0023] The method for preparing the lithium titanium iron borate positive electrode material of the embodiment of the present invention comprises: mixing a lithium source, a boron source, a titanium source and an iron source by ball milling, and then calcining and crushing to obtain the lithium titanium iron borate positive electrode material.

[0024] The preparation method of the lithium titanium iron borate positive electrode material of the embodiment of the present invention adopts titanium element doping lithium iron borate. Titanium element doping can stabilize the crystal structure, inhibit the secondary growth of grains, accelerate the lithium ion extraction / embedding path, improve the migration efficiency, and can improve the electronic conductivity and ion conductivity of the lithium iron borate material. When used in a ternary battery, the safety, cycle performance and rate performance of the ternary battery can be improved. The preparation method of the embodiment of the present invention is simple and easy to operate, has high production efficiency, and is easy to promote and apply in industrial production.

[0025] In some embodiments, preferably, the molar ratio of lithium, iron, boron and titanium in the lithium source, iron source, boron source and titanium source is 1:0.5 to 1:0.5 to 1:0.2 to 0.4.

[0026] In the embodiment of the present invention, the molar ratio of each substance in the positive electrode material is optimized. The positive electrode material obtained with a suitable molar ratio has a stable structure and better electrical properties. If the content of elemental titanium is too high, the crystal structure of the material may be destroyed and the electrochemical properties of the material may be affected. If the content of elemental titanium is too low, the crystal structure of the material may be unstable and the performance of the battery may be reduced.

[0027] In some embodiments, preferably, the lithium source includes at least one of lithium hydroxide and lithium carbonate;

[0028] And / or, the iron source includes at least one of ferroferric oxide, ferrous oxide, and ferrous oxalate;

[0029] And / or, the boron source includes at least one of boric acid and boron trioxide;

[0030] And / or, the titanium source includes at least one of titanium tetrachloride and titanium dioxide.

[0031] In some embodiments, preferably, the ball milling mixing time is 3 to 12 hours, for example, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc.;

[0032] And / or, the high temperature calcination temperature is 500-1000°C, for example, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, etc.; the calcination time is 6-24h, for example, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.

[0033] In the embodiments of the present invention, a high temperature calcination temperature is preferably used. If the calcination temperature is too low, the material may not be fully crystallized, affecting the electrochemical performance; if the calcination temperature is too high, the crystal structure may be destroyed, affecting the electrochemical performance.

[0034] In some embodiments, preferably, the particle size D50 of the lithium titanium iron borate positive electrode material is 0.5-10 μm.

[0035] In the embodiment of the present invention, the particle size of the lithium titanium iron borate positive electrode material is preferably selected. If the particle size is too large, the conduction rate of lithium ions will be reduced, affecting the battery performance. If the particle size is too small, the material is prone to agglomeration, affecting the uniformity of the material and the battery performance.

[0036] The embodiment of the present invention also provides a lithium titanium iron borate positive electrode material, which is prepared by the above method.

[0037] The embodiment of the present invention further provides a positive electrode plate, comprising the lithium titanium iron borate positive electrode material prepared by the above method or the above lithium titanium iron borate positive electrode material.

[0038] In some embodiments, preferably, the positive electrode plate also includes lithium nickel cobalt manganese oxide.

[0039] In some embodiments, the mass proportion of lithium titanium iron borate positive electrode material in the positive electrode plate is 9.5-28.5%, and the mass proportion of lithium nickel cobalt manganese oxide is 66.5-85.5%.

[0040] An embodiment of the present invention further provides a ternary battery, comprising the above-mentioned positive electrode plate.

[0041] In some embodiments, the ternary battery includes a positive electrode sheet, a negative electrode sheet and a separator. The preparation process of the positive electrode sheet includes: slurrying the above-mentioned lithium titanium iron borate, lithium nickel cobalt manganese oxide, conductive agent and binder in a mass ratio of 9.5% to 28.5%: 66.5% to 85.5%: 1.5% to 2.5%: 2.5% to 3.5%, and then coating, rolling and sheeting to obtain a positive electrode sheet; the preparation process of the negative electrode sheet includes: mixing graphite, sodium carboxymethyl cellulose, styrene butadiene rubber and conductive carbon black to prepare a slurry, and then coating, rolling and sheeting to obtain a negative electrode sheet; the separator is a polyethylene separator. After further lamination, packaging, baking, injection, formation, aging and capacity separation, a highly safe ternary battery is obtained.

[0042] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.

[0043] Example 1

[0044] (1) Preparation of lithium borate titanium iron positive electrode material: lithium carbonate (Li2CO3), ferrous oxalate (FeC2O4), boric acid and titanium tetrachloride are weighed and mixed in a molar ratio of lithium, iron, boron and titanium of 1:1:0.6:0.3, and anhydrous ethanol is used as a dispersant. The mixture is ball milled for 6 hours to obtain a precursor. The precursor is calcined at 800°C in an air atmosphere for 16 hours, cooled naturally, lightly ground and sieved to obtain a lithium borate titanium iron positive electrode material with D50 = 3μm, which is stored in a desiccator.

[0045] (2) Preparation of positive electrode sheet: 19% of lithium titanium iron borate, 76% of NCM811 (nickel cobalt manganese), 2.5% of positive electrode binder polyvinylidene fluoride and 2.5% of positive electrode conductive agent conductive carbon black are weighed by mass. First, polyvinylidene fluoride is added to N-methylpyrrolidone solvent to prepare a slurry. Then, conductive carbon black is added to the slurry and stirred until uniform. Then, lithium iron phosphate and lithium iron silicate are added to the slurry and stirred until uniform. Finally, the slurry is coated on the current collector and dried to prepare the positive electrode sheet. The positive electrode sheets are obtained by rolling and slitting.

[0046] (3) Preparation of negative electrode sheet: 96% of graphite negative electrode material, 1.0% of negative electrode binder sodium carboxymethyl cellulose, 1.5% of negative electrode binder styrene butadiene rubber and 1.5% of negative electrode conductive agent conductive carbon black were weighed by mass. First, sodium carboxymethyl cellulose was added to deionized water to prepare a slurry. Then, conductive carbon black and graphite were added to the slurry and stirred until uniform. Then, styrene butadiene rubber was added to the slurry and stirred until uniform. Finally, the slurry was coated on the current collector and dried to prepare the negative electrode sheet. The negative electrode sheets were obtained by rolling and slitting.

[0047] (4) Preparation of battery cells: The positive and negative electrode sheets are vacuum-baked, stacked to form battery cells and encapsulated in aluminum-plastic film.

[0048] (5) Preparation of batteries: After the baked battery cell is injected with liquid, formed, aged, and divided into different capacities, a high energy density lithium iron phosphate battery is obtained.

[0049] Example 2

[0050] (1) Preparation of lithium borate titanium iron positive electrode material: lithium carbonate (Li2CO3), ferrous oxalate (FeC2O4), boric acid and titanium tetrachloride are weighed and mixed in a molar ratio of lithium, iron, boron and titanium of 1:1:0.8:0.2, and anhydrous ethanol is used as a dispersant. The mixture is ball milled for 3 hours to obtain a precursor. The precursor is calcined at 500°C in an air atmosphere for 24 hours, cooled naturally, lightly ground and sieved to obtain a lithium borate titanium iron positive electrode material with a D50 of 0.8μm, which is stored in a desiccator.

[0051] (2) Preparation of positive electrode sheet: 19% lithium titanium iron borate, 76% NCM811, 2.5% positive electrode binder polyvinylidene fluoride and 2.5% positive electrode conductive agent conductive carbon black are weighed by mass. First, polyvinylidene fluoride is added to N-methylpyrrolidone solvent to prepare a slurry. Then, conductive carbon black is added to the slurry and stirred until uniform. Then, lithium iron phosphate and lithium iron silicate are added to the slurry and stirred until uniform. Finally, the slurry is coated on the current collector and dried to prepare the positive electrode sheet. The positive electrode sheets are obtained by rolling and slitting.

[0052] (3) Preparation of negative electrode sheet: 96% of graphite negative electrode material, 1.0% of negative electrode binder sodium carboxymethyl cellulose, 1.5% of negative electrode binder styrene butadiene rubber and 1.5% of negative electrode conductive agent conductive carbon black were weighed by mass. First, sodium carboxymethyl cellulose was added to deionized water to prepare a slurry. Then, conductive carbon black and graphite were added to the slurry and stirred until uniform. Then, styrene butadiene rubber was added to the slurry and stirred until uniform. Finally, the slurry was coated on the current collector and dried to prepare the negative electrode sheet. The negative electrode sheets were obtained by rolling and slitting.

[0053] (4) Preparation of battery cells: The positive and negative electrode sheets are vacuum-baked, stacked to form battery cells and encapsulated in aluminum-plastic film.

[0054] (5) Preparation of batteries: After the baked battery cell is injected with liquid, formed, aged, and divided into different capacities, a high energy density lithium iron phosphate battery is obtained.

[0055] Example 3

[0056] (1) Preparation of lithium borate titanium iron positive electrode material: lithium carbonate (Li2CO3), ferrous oxalate (FeC2O4), boric acid and titanium tetrachloride were weighed and mixed in a molar ratio of lithium, iron, boron and titanium of 1:0.5:0.8:0.4, and anhydrous ethanol was used as a dispersant. The mixture was ball milled for 12 hours to obtain a precursor. The precursor was calcined at 1000°C in an air atmosphere for 6 hours, cooled naturally, lightly ground and sieved to obtain a lithium borate titanium iron positive electrode material with a D50 of 10, which was stored in a desiccator.

[0057] (2) Preparation of positive electrode sheet: 19% lithium titanium iron borate, 76% NCM811, 2.5% positive electrode binder polyvinylidene fluoride and 2.5% positive electrode conductive agent conductive carbon black are weighed by mass. First, polyvinylidene fluoride is added to N-methylpyrrolidone solvent to prepare a slurry. Then, conductive carbon black is added to the slurry and stirred until uniform. Then, lithium iron phosphate and lithium iron silicate are added to the slurry and stirred until uniform. Finally, the slurry is coated on the current collector and dried to prepare the positive electrode sheet. The positive electrode sheets are obtained by rolling and slitting.

[0058] (3) Preparation of negative electrode sheet: 96% of graphite negative electrode material, 1.0% of negative electrode binder sodium carboxymethyl cellulose, 1.5% of negative electrode binder styrene butadiene rubber and 1.5% of negative electrode conductive agent conductive carbon black were weighed by mass. First, sodium carboxymethyl cellulose was added to deionized water to prepare a slurry. Then, conductive carbon black and graphite were added to the slurry and stirred until uniform. Then, styrene butadiene rubber was added to the slurry and stirred until uniform. Finally, the slurry was coated on the current collector and dried to prepare the negative electrode sheet. The negative electrode sheets were obtained by rolling and slitting.

[0059] (4) Preparation of battery cells: The positive and negative electrode sheets are vacuum-baked, stacked to form battery cells and encapsulated in aluminum-plastic film.

[0060] (5) Preparation of batteries: After the baked battery cell is injected with liquid, formed, aged, and divided into different capacities, a high energy density lithium iron phosphate battery is obtained.

[0061] Example 4

[0062] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (2), the mass ratio of lithium titanium ferroborate is 28.5%, and the mass ratio of NCM811 is 66.5%.

[0063] Example 5

[0064] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (2), the mass ratio of lithium titanium ferroborate is 9.5%, and the mass ratio of NCM811 is 85.5%.

[0065] Comparative Example 1

[0066] The preparation method of this comparative example is the same as that of Example 1, except that step (1) is eliminated, and in step (2): 95% of NCM811, 2.5% of positive electrode binder polyvinylidene fluoride and 2.5% of positive electrode conductive agent conductive carbon black are weighed by mass, polyvinylidene fluoride is first added to N-methylpyrrolidone solvent to prepare a glue solution, conductive carbon black is then added to the glue solution and stirred until uniform, and then lithium iron phosphate and lithium iron silicate are added to the slurry and stirred until uniform; finally, the slurry is coated on a current collector and dried to prepare a positive electrode sheet; and small positive electrode sheets are obtained by rolling and slitting.

[0067] Comparative Example 2

[0068] The preparation method of this comparative example is the same as that of Example 1, except that step (1) is eliminated, and in step (2): 19% of lithium iron borate, 76% of NCM811, 2.5% of positive electrode binder polyvinylidene fluoride and 2.5% of positive electrode conductive agent conductive carbon black are weighed by mass, polyvinylidene fluoride is first added to N-methylpyrrolidone solvent to prepare a glue solution, conductive carbon black is then added to the glue solution and stirred until uniform, and then lithium iron phosphate and lithium iron silicate are added to the slurry and stirred until uniform; finally, the slurry is coated on a current collector and dried to prepare a positive electrode sheet; and small positive electrode sheets are obtained by rolling and slitting.

[0069] The performance of the ternary batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 2 was tested. The results are shown in Table 1. The test methods for each performance are as follows:

[0070] (1) The positive electrode sheet resistance is tested using a film resistance meter;

[0071] (2) Charge to 4.2V at 1C constant current and constant voltage, cut off current 0.05C, and then discharge to 2.5V at 1C constant current, and measure the capacity retention rate of 500 cycles at room temperature / %; wherein the capacity retention rates of Example 1, Comparative Example 1 and Comparative Example 2 are as follows Figure 1 shown.

[0072] (3) Energy density is calculated based on capacity × voltage / battery mass;

[0073] (4) Needle puncture pass rate: in accordance with GB31485-2020 Safety requirements and test methods for power batteries for electric vehicles.

[0074] Table 1

[0075]

[0076]

[0077] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0078] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium titanium iron borate positive electrode material, characterized in that: include: The lithium source, boron source, titanium source and iron source are ball-milled and mixed, and then calcined and crushed to obtain a lithium titanium iron borate positive electrode material.

2. The method for preparing the lithium titanium iron borate positive electrode material according to claim 1, characterized in that: The molar ratio of lithium, iron, boron and titanium in the lithium source, iron source, boron source and titanium source is 1:0.5 to 1:0.5 to 1:0.2 to 0.

4.

3. The method for preparing the lithium titanium iron borate positive electrode material according to claim 1 or 2, characterized in that: The lithium source includes at least one of lithium hydroxide and lithium carbonate; And / or, the iron source includes at least one of ferroferric oxide, ferrous oxide, and ferrous oxalate; And / or, the boron source includes at least one of boric acid and boron trioxide; And / or, the titanium source includes at least one of titanium tetrachloride and titanium dioxide.

4. The method for preparing the lithium titanium iron borate positive electrode material according to claim 1, characterized in that: The ball milling mixing time is 3 to 12 hours; And / or, the high temperature calcination temperature is 500-1000° C., and the calcination time is 6-24 hours.

5. The method for preparing the lithium titanium iron borate positive electrode material according to claim 1, characterized in that: The particle size D50 of the lithium titanium iron borate positive electrode material is 0.5-10 μm.

6. A lithium titanium iron borate positive electrode material, characterized in that: The method is prepared by the method according to any one of claims 1 to 5.

7. A positive electrode sheet, characterized in that: The invention comprises the lithium titanium iron borate positive electrode material prepared by the preparation method according to any one of claims 1 to 5 or the lithium titanium iron borate positive electrode material according to claim 6.

8. The positive electrode sheet according to claim 7, characterized in that: Also includes lithium nickel cobalt manganese oxide.

9. The positive electrode sheet according to claim 8, characterized in that: The mass proportion of lithium titanium iron borate positive electrode material in the positive electrode plate is 9.5-28.5%, and the mass proportion of lithium nickel cobalt manganese oxide is 66.5-85.5%.

10. A ternary battery, characterized in that: The invention comprises the positive electrode sheet as described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Process for producing lithium borate compound

    CN102348640A

  • Lithium iron titanium phosphate negative electrode material, lithium titanate battery and preparation method of lithium iron titanium phosphate negative electrode material

    CN115881947A

  • Lithium manganese iron borate composite material as well as preparation method and application thereof

    CN117996046A